Legal Protection of Educators Against Criminalization in the Enforcement of Student Discipline - Laurentius Ni; Adrianus Marselus Nggoro (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze legal protection for educators against the threat of criminalization in the implementation of student discipline. The main issue lies in the antinomy between laws protecting the teaching profession and child protection laws, which often creates legal uncertainty. The method used is normative legal research with a Systematic Literature Review (SLR) approach based on the PRISMA protocol applied to scientific literature. The results show that the criminalization of teachers is triggered by the failure to distinguish between educational disciplinary actions (animus corrigendi) and acts of violence (animus nocendi), as well as a law enforcement approach that tends to be overly legalistic without considering pedagogical dimensions. Weak implementation of norms and social pressures further exacerbate the situation. This study concludes that there is a need to reconstruct the legal paradigm by affirming protection for proportional disciplinary actions, as well as strengthening professional ethical mechanisms and justice-based approaches to prevent excessive criminalization of educators.